The complex construction of a glaciovolcanic ridge with insights from the 2021 Fagradalsfjall Eruption (Iceland) - Pollock, Meagen; Edwards, Benjamin R.; Judge, Shelley; Wallace, Chloe; Hiatt, Alex; Perpalaj, Aleksander; Was, Ellie; Hauksdóttir, Steinunn (Frontiers in Earth Science, 2023)
Glaciovolcanic landforms provide global-scale records of paleoenvironmental conditions and yield insights into subglacial eruption processes. Models for the formation of glaciovolcanic ridges, or tindars, are relatively simple, proposing a monogenetic eruption and a fairly uniform stratigraphy with or without a single transition from effusive pillow lavas to explosive fragmental deposits. Others have suggested that tindars are more complicated. To build a more robust model for tindar formation, we conducted a field and geochemical study of Undirhlíðar ridge on the Reykjanes Peninsula in southwestern Iceland. We show that the ridge was built through a complex sequence of eruptive and intrusive events under dynamically changing ice conditions. Quarry walls expose a continuous cross-section of the ridge, revealing multiple pillow and fragmental units. Pillow lava orientations record the emplacement of discrete pillow-dominated lobes and the migration of volcanic activity between eruptive vents. Volatile contents in glassy pillow rinds show repeated pulses of pillow lava emplacement under glaciostatic conditions, with periods of fragmentation caused by depressurization. Variations in major elements, incompatible trace element ratios, and Pb-isotopes demonstrate that the eruption was fed from separate crustal melt reservoirs containing melts from a compositionally heterogeneous mantle source. A shift in mantle source signature of pillow lavas suggests that the primary ridge-building phase was triggered by the injection of magma into the crust. Within the growing edifice, magma was transported through dykes and irregularly shaped intrusions, which are up to 20% by area of exposed stratigraphy sequences. The model for tindar construction should consider the significant role of intrusions in the growth of the ridge, a detail that would be difficult to identify in natural erosional exposures. The 2021–22 eruptions from the adjacent Fagradalsfjall vents allow us to draw parallels between fissure-fed eruptions in subaerial and ice-confined environments and test hypotheses about the composition of the mantle underlying the Reykjanes Peninsula. Both Fagradalsfjall and Undirhlíðar ridge eruptions may have occurred over similar spatial and temporal scales, been triggered by mixing events, erupted lavas with varying mantle source signatures, and focused volcanic activity along migrating vents. Differences in composition between the two locations are not related to systematic lateral variations in the underlying mantle. Rather, the Undirhlíðar ridge and Fagradalsfjall eruptions capture complex interactions among the crustal magma plumbing system, mantle source heterogeneity, and melting conditions for a moment in time.